Nanocrystalline titanium oxide thin films prepared by sol-gel process - Viana,Marcelo M. (2006)
Crystalline films of pure titanium oxide have been prepared on soda lime slide glasses by sol-gel process and dip-coating. The definition of various parameters such as chemical concentration, viscosity, catalyst type and withdrawal speed led to the preparation of transparent, crystalline and adherent coatings with hydrophobic characteristics. Their crystalline structure was evaluated as anatase phase by low angle X-ray diffraction. Thicknesses were measured by perfilometry, and the refractive indices were determined from transmittance spectrum taking into consideration the layers deposited onto the two sides of the substrate. Porosity was also estimated by UV-visible spectroscopy by using the Lorentz - Lorenz equation. The average grain size was evaluated by atomic force microscopy. The thicker and denser films presented hydrophobicity, which decreased when the film porosity increased.